Analysis of the Effect of Taking Anti-Tuberculosis Drugs (ATD) on Blood Glucose Levels and Urine Protein Levels in Tuberculosis Sufferers at the Dasan Tapen Community Health Center, West Lombok - Wahyuni, Leni; Agrijanti, Agrijanti; Srigede, Lalu (Jurnal Analis Medika Biosains (JAMBS), 2024)
Tuberculosis is a contagious infectious disease caused by the bacteria Mycobacterium tuberculosis or often called Acid-Fast Bacteria (AFC). Tuberculosis positive patients must undergo treatment by administering category 1 Anti-Tuberculosis Drugs (ATD) for approximately 6-8 months. Anti-Tuberculosis Drugs (ATD) are divided into two phases, namely the intensive phase and the advanced phase. Consuming Anti-Tuberculosis Drugs (ATD) for a long period of time can cause the drug to become toxic in the body, so that it can affect body organs such as the kidneys and pancreas. The aim of this study was to measure blood glucose levels, measure urine protein levels and analyze blood glucose levels and urine protein levels in tuberculosis sufferers who took Anti-Tuberculosis Drugs (ATD). Using analytical observational research methods with a cross sectional research design . Tuberculosis sufferers are checked for blood glucose and urine protein, first and second collection. The results of research on 24 tuberculosis patients who took Anti-Tuberculosis Drugs (ATD) at the Dasan Tapen Community Health Center, West Lombok showed that the blood glucose levels of tuberculosis patients who took intensive phase ATD, namely of the 14 patients, 9 patients experienced an increase. Meanwhile, in the continuation phase, of the 10 patients, there were 6 patients who experienced improvement. The urine protein levels of tuberculosis sufferers who consumed ATD in the intensive and follow-up phase of the first examination were positive (+1) in 1 sample while negative (-) in 23 samples. In the second examination, 2 samples were positive (+1), while 22 samples were negative (-). The conclusion of this study is that there is no relationship between the first and second examination of random blood glucose levels and random urine protein levels.